The Influence of Implementation of Transformational and Democratic Leadership Styles On Job Loyalty of Employees at Airport Operation & Service Pt Angkasa Pura Aviasi Kualanamu International Airport Deli Serdang - Tampubolon, Yanti Mahdalena; You She Melly Anne Dharasta (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
The aim to be achieved is to analize and find out the magnitude, both partially and simultaneously, of the influence of transformational and democratic leadership styles on employee work loyalty. Classifed as quantitative research utilizing research instrument in the form of a questionnaire of 35 respondents (a saturated sample) of Airport Operation and Service employees of PT Angkasa Pura Aviasi Kualanamu International Airport Deli Serdang. Data were analyzed using SPSS version 26 with descriptive analysis techniques, classic assumption tests, and hypothesis tests. Employee work loyalty can be increased based on the findings of this research when transformational leadership style and democratic leadership style are implemented